Investigation on optimal filler loadings for dielectric strength enhancement of epoxy/TiO2@SiO2 nanocomposite. (27th March 2019) - Awais, Muhammad; Sundararajan, Raji; Sajjad, Intisar Ali; Haroon, Shaikh Saaqib; Amin, Salman; Shaukat, Hammad; Nasir, Muhammad Ali
Abstract: Insulation plays a critical role in all electrical systems. Ever increasing voltages in power system demand conscientious research on insulation materials. To enhancing the electrical/mechanical properties of insulation materials, nano composite polymer insulations materials are of main interest for researchers since last two decades. This study presents the dielectric properties of an epoxy nano composite with filler consisting of TiO2 nano particles encapsulated in SiO2 core–shell. The particular combination used in this study is only reported once in an earlier research. In previous research filler, concentration range was from 0% to 4% by weight and it was reported that less than 1% loading gives best results. This key objective of this work was to find a precise filler loading value below 1%, which could give highest dielectric strength of resulting epoxy nano composite. The range investigated in this work was from 0.3% to 0.8% by weight. This range has never been investigated in literature previously. Electrical and chemical characterizations of prepared epoxy nano composites was carried out by using SEM, EDX, leakage current, resistivity, relative permittivity and dielectric strength analysis. The best results were achieved at 0.6% filler loading in base epoxy. A decrease in dielectric strength was observed in filler loading exceeding 0.6%, which is due to hydrophilic nature of TiO2 @SiO2 which starts to dominate at higher loadings. In addition to this, uniform dispersion of nano-filler is a key requirement to get all the benefits of a formulated nano composite.